Analisis Manajemen Laba dan Profitabilitas Terhadap Tax Avoidance: Dampak Moderasi Ukuran Perusahaan - Indriyani, Indriyani; Handayani, Yenny Dwi (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
The purpose of this study is to examine the effect of earnings management and profitability on tax avoidance with company size as a moderating variable. The sample used in this study was 21 mining companies listed on the Indonesia Stock Exchange for the period 2018 - 2021 with purposive sampling as the sampling method. This study uses regression analysis with moderate regression analysis (MRA). The results of this study indicate that earnings management has no effect on tax avoidance, profitability has a negative effect on tax avoidance, company size has no effect on tax avoidance, company size cannot moderate the effect of earnings management on tax avoidance and company size cannot moderate the effect of profitability on tax avoidance.